A comparative study of conjunctival autograft with fibrin glue or glueless sutureless conjunctival autograft after pterygium surgery - Jain, Kalpna; Manoher, J. M. (International Journal of Research in Medical Sciences, 2018)
Background: Conjunctival autografting after Pterygium excision can be done by fibrin glue or sutures but use of foreign material can cause discomfort and infection. Fibrin glue may cause hypersensitivity reaction and also have risk of viral transmission. To avoid these conjuctival autograft can be applied without suture or glue. Patient’s own blood act as a bioadhesive. Methods: We done a prospective randomized control study of 70 patients, 35 patients allocated in each group. Group A had conjunctival autograft with fibrin glue while group B had conjunctival autografting without glue or sutures. Results: In group A 31 and group B 26 patients had well placed conjunctival autograft while 4 in group A and 9 patients in group B had either displaced or dislodged graft. The results were statistically insignificant with P value of 0.219 and No complication was reported in any patient except recurrence. The 5 patients in group A and 6 in group B had recurrence which is not statistically significant. Conclusions: Graft stability is more with fibrin glue as compare to glueless and sutureless conjunctival autografting but using patients own blood as bioadhesive is safer and cost effective. The rate of recurrence is similar in both the groups.